2011
DOI: 10.1002/cjoc.201190179
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of 2‐Arylamino‐2‐imidazolines and 2‐Ami‐ nobenzimidazoles with Aminoiminomethanesulfonic Acid Derivatives

Abstract: A highly efficient synthesis of 2-arylamino-2-imidazolines and 2-aminobenzimidazoles from aminoiminomethanesulfonic acid derivatives is described. The method is simple and practical, generating imidazoline and benzimidazoline derivatives in excellent isolated yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In 2011, Zhang et al reported another synthesis of 2-imidazolines from the reaction of ethylenediamine (34) with aromatic nitriles (33) (Scheme 8). [32] This synthetic approach was assisted by reusable cupric indole-3-acetate (Cu(II)-(IAA) 2 ) catalyst in the solvent-free condition under either reflux or microwave irradiation.…”
Section: Methods A: Synthesis Of Imidazolines From 12-diaminesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, Zhang et al reported another synthesis of 2-imidazolines from the reaction of ethylenediamine (34) with aromatic nitriles (33) (Scheme 8). [32] This synthetic approach was assisted by reusable cupric indole-3-acetate (Cu(II)-(IAA) 2 ) catalyst in the solvent-free condition under either reflux or microwave irradiation.…”
Section: Methods A: Synthesis Of Imidazolines From 12-diaminesmentioning
confidence: 99%
“…Mohanazadeh et al demonstrated the synthesis of 2-arylamino-2-imidazolines (46) from a reaction between amino(phenylimino)methanesulfonic acid derivatives (44) and ethylenediamine (45) under mild reaction conditions (Scheme 12). [34] The reaction used 2-propanol or water as reaction medium, where 2propanol affords better yields (80-93%) of the imidazoline products (yields in water 54-77%). Under optimized conditions, only halogen-substituted (p-ClPh, p-BrPh, 2,6-Cl 2 Ph) aromatic moieties were incorporated in the acid derivates.…”
Section: Methods A: Synthesis Of Imidazolines From 12-diaminesmentioning
confidence: 99%
“…The aromatic part of 1,2-dihydrobenzo[4,5]imidazo[1,2- a ]pyrazin-3(4 H )-ones II , benzimidazoles, were synthesized several times, in solution and on solid phase. Benzimidazole derivatives can serve as angiotensin II receptor antagonists, as inhibitors of trypsin-like serine protease (factor Xa), and as antibacterial agents . The synthesis of benzimidazolines and their closely related compounds, 2-oxo/thioderivatives and spiro-benzimidazolines, has also been described. , …”
Section: Introductionmentioning
confidence: 99%
“…The syntheses of diaminomethanesulfonic acid under other conditions based on this method were reported in some of the literature (Scheme A). In addition to this route, diaminomethanesulfonic acid was also synthesized from thiourea with several different conditions (Scheme B). …”
Section: Summary Of Synthetic Methods Of Diaminomethanesulfonic Acidmentioning
confidence: 99%
“… a (a) AcOOH, AcOH, −20 °C, ambient temperature, 2 h; , (b) H 2 O 2 , 20 °C, 2 h; (c) AcOOH, MeOH, 24 h, ambient temperature; (d) Na 2 MoO 4 , H 2 O 2 , NaCl, H 2 O, 0–30 °C; (e) H 2 SO 4 , H 2 O 2 , Ac 2 O, MeOH, H 2 O, 20 °C, 48 h; (f) HCl, H 2 SeO 3 …”
Section: Summary Of Synthetic Methods Of Diaminomethanesulfonic Acidmentioning
confidence: 99%